2018
DOI: 10.1016/j.ijantimicag.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Current antifungal treatment of fusariosis

Abstract: Fungi of the genus Fusarium are well known as major plant pathogens and soil inhabitants, but also cause a broad spectrum of human infections. Fusariosis is the second most common mould infection after aspergillosis, and keratitis is the most encountered implantation infection in immunocompetent individuals. Natamycin is active against Fusarium species both in vitro and in vivo, and is used along with voriconazole as the mainstay of treatment for Fusarium keratitis. Onychomycosis is treated with terbinafine, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
108
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 91 publications
(117 reference statements)
4
108
0
5
Order By: Relevance
“…Many studies have reported data on the poor in vitro activity of amphotericin B, itraconazole, and echinocandins against clinical Fusarium strains, with MIC values similar to those in our findings (9,10,18,(26)(27)(28). Regarding the poor outcome with monotherapy and in view of the reported synergistic interactions of some agents, such as, liposomal amphotericin B with terbinafine (4), amphotericin B with voriconazole (29), and natamycin with voriconazole (9), combination therapy is recommended (1,18). In the current study, all clinical Fusarium isolates showed low MICs of Յ0.125 g/ml for luliconazole and Յ1 g/ml for lanoconazole.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Many studies have reported data on the poor in vitro activity of amphotericin B, itraconazole, and echinocandins against clinical Fusarium strains, with MIC values similar to those in our findings (9,10,18,(26)(27)(28). Regarding the poor outcome with monotherapy and in view of the reported synergistic interactions of some agents, such as, liposomal amphotericin B with terbinafine (4), amphotericin B with voriconazole (29), and natamycin with voriconazole (9), combination therapy is recommended (1,18). In the current study, all clinical Fusarium isolates showed low MICs of Յ0.125 g/ml for luliconazole and Յ1 g/ml for lanoconazole.…”
supporting
confidence: 90%
“…Moreover, MIC 90 values of luliconazole, lanoconazole, and other tested drugs for the environmental Fusarium isolates were completely similar to those of the clinical isolates, with the exception of better activities of efinaconazole (MIC 90 , 1 g/ml) in environmental isolates and lanoconazole (0.64 g/ml) in clinical isolates (Table 1). Many studies have reported data on the poor in vitro activity of amphotericin B, itraconazole, and echinocandins against clinical Fusarium strains, with MIC values similar to those in our findings (9,10,18,(26)(27)(28). Regarding the poor outcome with monotherapy and in view of the reported synergistic interactions of some agents, such as, liposomal amphotericin B with terbinafine (4), amphotericin B with voriconazole (29), and natamycin with voriconazole (9), combination therapy is recommended (1,18).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Despite the concerns about in vitro antagonism between polyenes and azoles, some studies have shown in vitro synergism of voriconazole and L-AMB against Fusarium [25]. Based on such studies and on few clinical reports of success in the treatment of invasive fusariosis with the association of L-AMB with voriconazole, some authors support CAT for fusariosis [26][27][28][29]. In this case series 1 patient with invasive fusariosis was successfully treated with L-AMB associated with voriconazole.…”
Section: Discussionmentioning
confidence: 86%
“…For example, F. solani species complex and F. verticillioides may be resistant to triazoles and exhibit higher amphotericin B MICs than other Fusarium species. 61,70 Fusarium species are intrinsically resistant to echinocandins. Interpretive breakpoints are not defined given a lack of data correlating in vitro susceptibility to clinical outcome; however, epidemiological cut-off values were recently established.…”
Section: Management and Outcomementioning
confidence: 99%